Efficiency VS Halal: Mechanical Animal Slaughter From a Maslahat Perspective - Permata, Cahaya; Irham, Muhammad Iqbal; Hamdani, Muhammad Faisal (Journal Analytica Islamica, 2025)
Mechanical animal slaughter is an innovation that has an impact on the efficiency of modern food industry production while maximizing the fulfillment of people's needs for meat. On the other hand, mechanical slaughter also creates problems related to its halalness. This study aims to analyze and identify aspects of Islamic law related to the halalness of mechanical slaughter and examine the considerations of Islamic law on its efficiency based on maslahat. As doctrinal research, this study is descriptive with an approach to the concept of maslahat and laws and regulations. Data related to the concept of halal animal slaughter and the concept of maslahat, which are integrated with applicable laws and regulations, are collected from the library, processed and analyzed comprehensively using qualitative methods. This study has implications for the use of mechanical slaughter methods to meet the halal standards set by Islam with consideration of the efficiency offered by the modern food industry. The results of the study indicate that mechanical animal slaughter can increase production efficiency, especially time and cost. This efficiency has challenges in ensuring the halalness of the product, especially those related to slaughtering according to sharia, mentioning the name of Allah and the state of consciousness of the animal. Based on the benefits, the use of technology is acceptable as long as there is certainty that the mechanical slaughtering process does not conflict with Islamic law. Mechanical slaughtering still requires stricter regulation and supervision to ensure that the efficiency of slaughtering carried out in the modern food industry is in accordance with the principles of halal.